Implementation of the Project Based Learning Model in Science Learning on the Growth and Development of Living Things in Grade III of Elementary School - Nur Kholisa Aprilia; Arina Izza Mardlatillah; Faroh Diah Ulfa Safitri; Wafiqoh Ramadhani (Penerbit Presisi Pustaka, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in science learning related to the growth and development of living things in third-grade students at SDN Talang 3, and to analyze its success rate. This study used a qualitative approach with data collection methods through interviews, observation, and documentation. The implementation of PjBL was carried out through several stages: project planning, observing plant growth, recording daily data, presenting results, and conducting learning reflections. The results showed that the implementation of PjBL achieved a success rate of 90%. This performance was measured based on the achievement of learning objectives, active student involvement, collaborative skills, the quality of project results, and students' conceptual understanding. The PjBL model has been proven to improve understanding of science concepts and develop 21st-century skills such as critical thinking, creativity, collaboration, and communication. Although there were some technical obstacles in the project process, the teacher's role as an active facilitator successfully overcame these problems. Thus, PjBL can be implemented effectively in science learning at the elementary school level and is in accordance with the Independent Curriculum.